Back Cover: Polyoxometalate/Polyethylene Glycol Interactions in Water: From Nanoassemblies in Water to Crystal Formation by Electrostatic Screening (Chem. Eur. J. 35/2017). Issue 35 (21st April 2017) - Buchecker, Thomas; Le Goff, Xavier; Naskar, Bappaditya; Pfitzner, Arno; Diat, Olivier; Bauduin, Pierre
Abstract : In the present work it is shown that the well‐known α‐Keggin polyoxometalate, α‐PW12 O40 3− (PW), forms hybrid crystalline materials with industrial (neutral) polyethylene glycol oligomers (PEG) under mild conditions, that is, in aqueous medium and at room temperature. The formation of these materials originates from the spontaneous self‐assembly of PW with EO x with at least four EO units ( x ≥ 4). Addition of NaCl induces the collapse of the nanoassemblies and the formation of hybrid crystalline materials. More information can be found in the Full Paper by P. Bauduin et al. onpage 8434 .